2010
DOI: 10.1017/s1368980010002302
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect association between environmental factors and fruit intake, mediation by psychosocial factors: the Pro Children study

Abstract: Objectives: To explore direct associations between home and school availability of fruit and fruit intake, and the mediating role of attitude towards fruit, liking, perceived barriers and self-efficacy. Design: Cross-sectional study. Setting: Primary schools in nine European countries. Subjects: Within the Pro Children study, data were collected on perceived home and school availability of fruit, psychosocial factors related to fruit intake and its frequency among 13 305 11-year-old schoolchildren. Results: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Research has been conducted in older children supporting this finding 49 50. Wind et al 51 also found cutting up vegetables correlated to children's intake. This study is the first study conducted in primary school children in the UK to support such findings.…”
Section: Discussionmentioning
confidence: 80%
“…Research has been conducted in older children supporting this finding 49 50. Wind et al 51 also found cutting up vegetables correlated to children's intake. This study is the first study conducted in primary school children in the UK to support such findings.…”
Section: Discussionmentioning
confidence: 80%
“…The Pro Children study, conducted with 11-year-old children in Europe, found that liking fruit and self-efficacy were both significant mediators of the relationship between fruit availability at home and fruit consumption. [20] The authors concluded that fruit intake is not a completely automatic or unconscious behavior and cognitive factors may be an important target for interventions to improve eating behavior in children in combination with efforts to improve the food environment.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal and cross-sectional studies both show that exposure to and availability and accessibility of healthy foods can increase the preference for and intake of these foods (Pearson, Biddle, & Gorely, 2009;Ventura & Birch, 2008;Wind, te Velde, Brug, Sandvik, & Klepp, 2010). Conversely, research has also shown that a permissive style of parenting that allows for availability of unhealthy food products at home is linked to children eating more total fat, sugar, and 'junk food,' and consuming more soft drinks (Gable & Lutz, 2000;Haerens, et al, 2008;McClain, Chappuis, Nguyen-Rodriguez, Yaroch, & Spruijt-Metz, 2009).…”
Section: Availability Of Healthy or Unhealthy Foodsmentioning
confidence: 99%